The Velocity and Initiation Time for the Streamer Discharge with in Dielectric Liquids - Khalaf, Thamir H (Al-Nahrain Journal of Science, 2018)
Dielectric liquids are widely used in high voltage equipments such as transformers. This study reports the computational results for some parameters that affect the initiation time and velocity of the streamer discharge within some dielectric liquids between pin-plane electrodes. Finite element technique was used to indicate the electric field distribution within a dielectric liquids. Results show clearly that, the applied voltage and the liquid permittivity affect (increasing or decreasing) the values of the initiation time and the velocity of the streamer.